Consider others better than yourself: social decision-making and partner preference in borderline personality disorder - Jeung, Haang; Vollmann, Martin; Herpertz, Sabine; Schwieren, Christiane (Journal of behavior therapy and experimental psychiatry, 2020)
Background and objectives - Patients with Borderline Personality Disorder (BPD) suffer from interpersonal difficulties. They have been shown to be distrustful and yet involved in abusive relationships. In this study, we want to examine whether the perception of fairness and partner preference are altered in BPD. - Methods - We employed a coalition formation game in which a participant can choose whether to interact in dyads or triads, thus exclusion or inclusion of a third potential interaction partner. Furthermore, triads get a higher endowment, such that dyads are not only unfair to one partner, but also economically inefficient, as the participant reduces the overall amount of money available for distribution. Subsequently, we compared how participants predicted another person's game strategy (inclusive, exclusive, or mixed) and rated its fairness, and which partner the participant would select. - Results - The majority of the BPD group (n=26) as well as of the healthy group (n=29) preferred triads over dyads and offered a near-to-equal split to their interaction partners in the first two rounds. In contrast to the healthy group, the BPD group did not show a drop of the average level of investment in the final round. In both groups, the inclusive strategy was perceived as the fairest strategy. Most interestingly, despite a similar perception of fairness, half of the BPD group preferred an interaction partner with an exclusive or mixed strategy while the majority of the HC group would choose an interaction partner with an inclusive strategy. - Limitations - This is a preliminary study which needs further replications before strong conclusions can be drawn. - Conclusions - Our study demonstrates no differences in fairness perception but an alteration in partner preference of patients with BPD which might contribute to unfavorable partner choices and impairments of interpersonal functioning in BPD.